Focus on Alectinib and Competitor Compounds for Second-Line Therapy in ALK-Rearranged NSCLC - Tran, Phu N.; Klempner, Samuel J. (Frontiers in Medicine, 2016)
The management of anaplastic lymphoma kinase rearranged (ALK+) non-small cell lung cancer (NSCLC) exemplifies the potential of a highlights the success of the precision medicine approach to cancer careparadigm. The ALK inhibitor crizotinib has demonstrated led to improved outcomes in the first and second line setting, however, toxicities, intracranial activity and acquired resistance necessitated the advent of later generation ALK inhibitors. A large portion of acquired resistance to ALK inhibitors is caused by secondary mutations in the ALK kinase domain. Alectinib is a second generation ALK inhibitor capable of overcoming multiple crizotinib resistant ALK mutations and has demonstrated improved outcomes after crizotinib failure, leading to approval in crizotinib treated ALK+ NSCLC patients. Favorable toxicity profile and improved intracranial activity haves spurred ongoing front line trials and comparisons to other ALK inhibitors. However, important questions regarding comparability to competitor compounds, acquired alectinib resistance, and ALK-inhibitor therapy sequencing remain. Here, we review the key clinical data supporting alectinib in the second line therapy of ALK+ NSCLC and provide context in comparison to other ALK inhibitors in development.